Analysis of Behaviour, Social Support and Motivation of Jumantik Cadre to Dengue High Fever (DHF) Entomological Index in the Pesantren 1 Public Health Center Kediri City - Suwarsi Suwarsi; Nurwijayanti Nurwijayanti (Journal for Quality in Public Health, 2021)
The occurrence of DHF outbreaks is indicated because the vector population of Aedes aegypti is increasing, this mosquito is an insect that always causes problems, its role as a vector carrier of disease can cause serious problems.. The purpose of this research is to analyze influence jumantik cadres on the DHF entomology index in the Work Area of ​​the Pesantren 1 Public Health Center, Kediri. The design of this study is a quantitative analytic study with a cross sectional approach with the focus of the research being aimed at analyzinginfluence behavior, social support and motivation of jumantik cadres on the DHF entomology index in the Work Area of ​​the Pesantren 1 Public Health Center Kediri City with a population of 161 respondents and a sample of 115 respondents drawn by technique Simple Random Sampling.The findings show that hAlmost half of the respondents have a good behavior category as many as 52 respondents (44.8%). Nearly half of the respondents 53 respondents (45.7%) have good category social support. Almost half of the respondents have high category motivation as many as 51 respondents (44%). Nearly half of the respondents 51 respondents (44%) rated their region's entomological index in the medium risk category. Based on the results of the Multiple Linear Regression analysis, it shows that with a p-value of 0.000 <0.05, H1 is accepted so it can be concluded that simultaneously there is an effectbehavior, social support and motivation towards DHF entomology index in the working area of ​​the Pesantren 1 Public Health Center Kediri City, the amount of influence is 71.1% Jumantik cadres must be able to carry out an entomological survey properly, where if they find larvae, they can immediately report them to the relevant party and immediately provide education to family members in the house so that they can help in 3M plus efforts and also reduce the incidence of houses with larvae in each. - each working area.